Media Content Preferences and Perceptions towards Dominant Value Orientations in Media Among Pre-Service Teachers - Mata, Suzette; Handang, Juspher; Joe, Nurfaiza; Saldariega, Lyka; Ruiz, Genelyn; Gregorio, Kathleen; Lapore, Nicole; Doren, Cherry Ann; Lemana, Jewel (Jurnal Pendidikan Progresif, 2023)
Media Content Preferences and Perceptions Towards Dominant Value Orientations in Media Among Pre-Service Teachers. Objective: The purpose of this study was to determine the media content preferences and the perceptions towards dominant value orientations in media. Methods: This research employed a quantitative research design through the use of an online survey technique. Findings: The findings showed that there are gender differences in relation to the pre-service teachers' thematic content preferences. In terms of the preferable television program content and the gender of pre-service teachers, it revealed a statistically significant difference. A positive and negative correlation was also shown between the pre-service teachers' viewing habits and their perceptions of dominant values that are presented in various television programs, and in the pre-service teachers' preferences for music genres and the values promoted in several music videos. Conclusion: The findings in this study indicate that the media content preferences of pre-service teachers differ from their perception of media values.  Keywords: media content preferences, perceptions, value orientations.DOI: http://dx.doi.org/10.23960/jpp.v13.i2.202315